KONTRIBUSI KREDIBILITAS TUTOR TERHADAP MOTIVASI BELAJAR WARGA BELAJAR PENDIDIKAN KESETARAAN PAKET C DI PKBM HARAPAN BANGSA KECAMATAN TAMBANG KABUPATEN KAMPAR - Nurul anisa; Daeng Ayub; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Formulation of the problem in this study is How much is the credibility of the tutor in PKBM Harapan Bangsa, Tambang District, Kampar Regency? How high is the motivation of learning citizens to learn about Equality in Package C education at PKBM Harapan Bangsa, Tambang District, Kampar Regency? Is there a significant positive contribution between the credibility of the tutor on the learning motivation of citizens learning the equality of package C in PKBM Harapan Bangsa, Tambang District, Kampar Regency. The purpose of this research is to find out and analyze how much the contribution of tutors' credibility to the motivation of learning in PKBM Harapan Bangsa, This research is a descriptive quantitative research of two variables. The population in this study were residents of package C, as many as 113 residents. Simple Random Sampling sampling technique. The instrument used was a questionnaire. Tutors' credibility and learning motivation each consists of 40 statements. Tutors' credibility is measured through indicators of expertise, trust, dynamism, sociability, coordination and charismatic. While learning motivation is measured through the existence of desires and desires to succeed, there are encouragement and needs in learning, the hopes and ideals of the future, the appreciation of learning, the existence of interesting activities in learning, the existence of a conducive learning environment. The credibility of the tutor to the learning motivation of citizens learning equality education in Package C in PKBM Harapan Bangsa is relatively high with a mean of 4.25. Based on inferential statistical analysis the tutors' credibility contribution to the learning motivation of learning citizens was obtained at a low of 14.50%. This means that there are still 85.50% caused by other factors not part of this study.Key Words: Contribution, Credibility, Motivation, Learning Citizens